The Interaction between Interregional Disparities and Immigration in Turkey - Ferhan Gezici; Berna Keskin (European Regional Science Association (ERSA), 2005)
The changing economic processes in the world have been affected on both the regions within a country and regions as a group of countries. In the regional development literature, although it is emphasized that globalization will enhance the development of advantages-rich regions, there are some other approaches assuming that increasing economic interaction and technological improvements will help to develop relatively less developed-peripheral regions as well. Furthermore, the studies, which are analyzing interregional disparities, put forward the significant impact of factor movements. Interregional migration has been considered as a significant issue of metropolitan regions on the one hand and the loss of workforce in the less-developed regions on the other hand. Migration has been one of the significant factors in order to explain the spatial aspects of economic development. The aim of this paper is, to evaluate inter-provincial migration related to their development levels and their geographical locations in Turkey. In order to measure the interaction between interregional disparities and migration pattern, the findings of regression analysis, which are constituted by using several socio-economic indicators, will be displayed. Furthermore, it is examined the assumption that geographical locations of provinces have an effect and cause not only their levels of development, but migration trends as well. Therefore, locating in the western regions, being a coastal province and being close to the metropolitan cities are the main locational advantages for immigration.
Keywords: 330